Autochthonous Gnathostomiasis in Madagascar - Annie Raharisoa (Emerging Infectious Diseases, 2020)
We used molecular tools to identify an autochthonous case of gnathostomiasis in Madagascar. This severe ocular infection, caused by Gnathostoma spinigerum nematodes, led to vision loss in the patient’s left eye. Clinicians should be aware of this parasitosis in Madagascar and other countries in Africa.